PENGEMBANGAN PERANGKAT PEMBELAJARAN PROBLEM POSING BERBANTUAN MIND MAPPING UNTUK SISWA SMP KELAS VII MATERI ARITMETIKA SOSIAL - Chandra, Fitriana Eka (FKIP Universitas Islam Jember, 2017)
This study reports a Research and Development (R&D) study which is aimed at developing educational product; mind mapping-assisted problem posing. The educational products developed in this study are lesson plan, students? consultation sheet, students? textbook, teacher?s book, and assessment sheet. This research and development (R&D) employed Four-D Model proposed by Thiagarajan. In this study, the researcher only employed three steps namely define, design, and development. It can be concluded that the developed educational products can be applied in the teaching-learning process in the classroom.Keywords: R&D, Problem Posing, Mind-Mapping, Educational Products.